FESTIVAL GEROBAK SAPI DI SLEMAN SEBAGAI AJANG JAWABAN SEBUAH TANTANGAN ZAMAN - Novitasari, Lisa Arum (Universitas Semarang, 2021)
Sleman people are indigenous people of Indonesia who live in Sleman Regency, DIY Province. They have various forms of art and traditional ceremonies that can still be found today. Cattle carts that used to serve as a means of transport, agricultural tools and plantations and transportation, now most cow carts have switched functions into tourist facilities. In Sleman, cow carts are often involved in the celebration of August 17, children's carnivals and schools, as well as marriage ceremonies. The changing times of the emergence of events involving Cow Carts is the Cow Cart Festival which is one form of traditional events held every year. This research aims to reveal the traditional festival activities of Cow Cart Sleman community as a phenomenon of the times in this case tradition that there are differences in the function of usefulness in the traditional era with the present / modern and reveal the cultural messages contained in it. The research approach is conducted qualitatively by observation method of participation through interviews with the owners of cow carts / bastards as well as following the activities carried out by the community in the tradition of the Festival. The results showed there are cultural messages that indicate the effectiveness of the utilization of resources, namely cows wisely with the form of cow cart festival that must be preserved so as not to become extinct.